PROKRASTINASI AKADEMIK PESERTA DIDIK KELAS XI DI SMA NEGRI 2 SUNGAI TARAB - Sulaiman Abdul Karim Elvag; Rina Yulitri; Emeliya Hardi; Hadiarni Hadiarni (Indonesian Journal of Counseling and Development, 2023)
The main problem in this study is that class XI students at SMA N 2 Sungai Tarab experience academic procrastination in both online and face-to-face learning, so this study aims to reveal the level of academic procrastination in SMA N 2 Sungai Tarab students and compare academic procrastination in face-to-face learning with online learning. This type of research is descriptive-quantitative, with a research sample of all students in class XI consisting of 63 students. The data were collected using a questionnaire and analyzed using descriptive statistical analysis. The results showed that of the 63 respondents, 32 students experienced academic procrastination with a high classification, 13 students with a moderate category, 17 with a low category, and one with a deficient category. The study results also show that the academic procrastination score in online learning is 12% higher than in face-to-face education.